2015
DOI: 10.1152/ajpcell.00332.2014
|View full text |Cite
|
Sign up to set email alerts
|

Induction of cardioprotection by small netrin-1-derived peptides

Abstract: Li Q, Cai H. Induction of cardioprotection by small netrin-1-derived peptides. Am J Physiol Cell Physiol 309: C100 -C106, 2015. First published April 29, 2015; doi:10.1152/ajpcell.00332.2014.-We have shown that netrin-1 induces potent cardioprotection via extracellular signal-regulated kinases 1 and 2 (ERK1/2)-dependent endothelial nitric oxide synthase (eNOS)/NO activation. The present study investigated cardioprotective effects of small netrin-1-derived peptides. We synthesized three laminin (Lam) V peptides… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…According to previous descriptions, netrin-1, mediated through different receptors, may regulate different signaling pathways and play distinct roles in physiological and pathophysiological conditions 13 . Other than the function of axon guidance, netrin-1 can also protect the kidney against ischemia-reperfusion injury, regulate angiogenesis, and even promote tumor growth 14 17 . In addition, netrin-1 was found recently to possess an anti-inflammatory capacity in lung injury and inflammatory peritonitis 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…According to previous descriptions, netrin-1, mediated through different receptors, may regulate different signaling pathways and play distinct roles in physiological and pathophysiological conditions 13 . Other than the function of axon guidance, netrin-1 can also protect the kidney against ischemia-reperfusion injury, regulate angiogenesis, and even promote tumor growth 14 17 . In addition, netrin-1 was found recently to possess an anti-inflammatory capacity in lung injury and inflammatory peritonitis 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to identify the minimal functional peptide that could preserve netrin-1 function in activating the receptor DCC and stimulating downstream signaling events. In this issue of the American Journal of Physiology-Cell Physiology, Cai's group extend their previous finding and identify a 9-amino acid (aa) core sequence in the laminin V region of netrin-1 to be highly effective in cardioprotection (5).…”
mentioning
confidence: 86%
“…Significantly, in preclinical studies, these synthetic peptides V1, V2, and V3 were observed to induce similar cardioprotection against I/R injury when compared with netrin-1 when either preperfused or simultaneously perfused to the heart. The data demonstrate that these peptides are consistently beneficial whenever they are delivered to the heart and have the potential to be developed as therapies for myocardial infarction (5).…”
mentioning
confidence: 88%
“…Nitric oxide (NO)—a key molecule preserving endothelial function—was identified as a major mediator of the cardioprotective effects of Ntn1. Ntn1 induces NO production through the DCC receptor followed by Erk and eNOS activation, and Ntn1 administration leads to a substantial NO-dependent reduction in myocardial infarct sizes ex vivo [ 42 , 98 ]. The concept of post-infarct tissue conservation by Ntn1 was further shown in diabetic mice [ 33 ].…”
Section: Myocardial Ischaemia–reperfusion Injury and Neuronal Guidancmentioning
confidence: 99%
“…The concept of post-infarct tissue conservation by Ntn1 was further shown in diabetic mice [ 33 ]. As the administration of small synthesized peptides containing Ntn1 domains successfully induced NO production in an animal model, pharmacological approaches have been developed to mimic the cardioprotective effects of Ntn1 [ 42 ]. The Ntn1–DCC–NO axis further attenuates mitochondrial superoxide production and preserves mitochondrial integrity in cardiomyocytes post-conditioned with Ntn1 after IR injury [ 8 , 9 , 76 ].…”
Section: Myocardial Ischaemia–reperfusion Injury and Neuronal Guidancmentioning
confidence: 99%